Prolidase could be considered a sign of inflammation associated with cigarette smoking - Yıldırım, Berna Botan; Kulaksızoglu, Sevsen (Frontiers in Medicine, 2024)
Objectives: Smoking causes inflammation, thickening, and narrowing of the airways. This inflammatory process is a reaction to free radicals and oxidants. Smoking affects collagen metabolism and tissue remodeling. Prolidase enzyme hydrolyzes iminodipeptides with hydroxyproline and C terminal proline. It plays a crucial role in the metabolism of collagen and the remodeling of the matrix.The present study aims to reveal the association of prolidase with inflammation caused by smoking and to compare serum prolidase levels with oxidative-antioxidative status in healthy individuals.Methods: A total of 76 participants (38 smokers and 38 nonsmokers) were involved in the present study. Serum cotinine levels were measured to show the exposure to nicotine in tobacco smoke by using the competitive inhibition enzyme immunoassay method. Serum prolidase, total oxidant status (TOS), and total antioxidant status (TAS) were determined by the enzyme-linked immunosorbent (ELISA) method, respectively. The correlation between smoking, serum prolidase levels, TOS, and TAS was investigated.Results: TAS and serum prolidase levels of smokers were considerably lower than those in nonsmokers (p<0.001, p=0.012 respectively). However, no differences were observed in TOS between the two groups. There was no statistically significant correlation between serum prolidase levels, TAS, and TOS. Moreover, no relationship was observed between respiratory function parameters and serum prolidase levels.To the best of our knowledge, the present study is the first study to demonstrate the role of prolidase in smoking-related inflammation. The results achieved in the present study suggest that smoking creates an imbalance in the oxidant-antioxidant activity. Smoking decreases prolidase levels, leading to decreased collagen turnover. Chronic pulmonary disease might be related to this decrease in collagen turnover.